MINIMALISASI DERATING BEBAN DAN TRIP BOILER AKIBAT OVERLOAD PADA MOTOR FCA DENGAN HAND AUTO (PEMBATASAN) DAMPER FCA - Dasman Dasman (Ensiklopedia of Journal, 2022)
Steam Power Plant (PLTU) is a thermal power plant that converts chemical energy in fuel into electrical energy, so that the electricity produced depends on fuel consumption. Ombilin PLTU supplied electricity of 16.44% to the Central Sumatra (Sumbagteng) transmission system, so Ombilin PLTU was required to maintain production stability by minimizing plant disruptions which resulted in derating. In general, PLTU consists of main systems (turbines, generators, transformers and boilers) and support systems (common). Combustion air requirement for 100% load required 2 FD Fan (forced press fan). To increase the operational reliability of FD Fan system, there are several things that are needed, among others, an alarm as a warning and a limiter as a safeguard for FD Fan system equipment. The addition of an alarm program and motor current limiting on the FD Fan aims to avoid overloading the FD Fan motor which results in derating and trip units.